FOLKTALES AS MEANINGFUL CULTURAL AND LINGUISTIC RESOURCES TO IMPROVE STUDENTS’ READING SKILLS - Mantra Ida Bagus Nyoman; Kumara Dewa Gede Agung Gana (Lingua Scientia, 2018)
Creating an English learning environment in which learners are highly motivated is sometimes very challenging for EFL teachers. Folktales can be useful for facilitating learners in their competence of English language and also for enhancing their cross-cultural awareness. In the field of language teaching, the richness and potential of folktales seems to have been under-utilized in today’s language classes. This paper explores how folktales can be used as a medium of improving students’ reading skills and major benefits in using folktales for teaching English.  A classroom action research was employed to attain the purpose of this study in which two cyclic learning sessions were conducted to improve English learners’ reading skills. Several selected Indonesian folktales were intensively utilized in reading classes. This result of this study indicates that use of folktales by EFL teachers could improve student’ reading skill and widen their vocabulary and at the same time, culture is acquired by the students.